Biofilm Morphotypes and Population Structure among Staphylococcus epidermidis from Commensal and Clinical Samples. - Llinos G Harris; Susan Murray; Ben Pascoe; James Bray; Guillaume Meric; Leonardos Mageiros; Thomas S Wilkinson; Rose Jeeves; Holger Rohde; Stefan Schwarz; Herminia de Lencastre; Maria Miragaia; et al. (PLoS ONE)
Bacterial species comprise related genotypes that can display divergent phenotypes with important clinical implications. Staphylococcus epidermidis is a common cause of nosocomial infections and, critical to its pathogenesis, is its ability to adhere and form biofilms on surfaces, thereby moderating the effect of the host's immune response and antibiotics. Commensal S. epidermidis populations are thought to differ from those associated with disease in factors involved in adhesion and biofilm accumulation. We quantified the differences in biofilm formation in 98 S. epidermidis isolates from various sources, and investigated population structure based on ribosomal multilocus typing (rMLST) and the presence/absence of genes involved in adhesion and biofilm formation. All isolates were able to adhere and form biofilms in in vitro growth assays and confocal microscopy allowed classification into 5 biofilm morphotypes based on their thickness, biovolume and roughness. Phylogenetic reconstruction grouped isolates into three separate clades, with the isolates in the main disease associated clade displaying diversity in morphotype. Of the biofilm morphology characteristics, only biofilm thickness had a significant association with clade distribution. The distribution of some known adhesion-associated genes (aap and sesE) among isolates showed a significant association with the species clonal frame. These data challenge the assumption that biofilm-associated genes, such as those on the ica operon, are genetic markers for less invasive S. epidermidis isolates, and suggest that phenotypic characteristics, such as adhesion and biofilm formation, are not fixed by clonal descent but are influenced by the presence of various genes that are mobile among lineages.